New species of earthworms from the genera Holoscolex and Glossodrilus (Crassiclitellata) in the Eastern Amazon - Hernández-García, Luis Manuel; Beckman, Ruana Aretha Farias Santiago; James, Samuel Wooster; Sousa, Sandriel Costa; Limeira-De-Oliveira, Francisco; Rousseau, Guillaume Xavier (Zootaxa, 2026)
We describe two new species of the earthworm genera Holoscolex and Glossodrilus from the Gurupi Biological Reserve, Maranhão State, Brazil. This reserve represents one of the last wild refuges of the Belém Endemism Area, the most deforested and threatened region of the Brazilian Amazon. Holoscolex contractilis sp. nov. belongs to a selected group of this genus characterized by intraclitellar atrial glands, and it is unique in having two pairs of spermathecae in segments 7 and 8, with atrial glands adjacent in 8 and 9, and free testes in segment 11. Glossodrilus rubra sp. nov. remains among the Glossodrilus species with two pairs of spermathecae in segments 8 and 9, but differs from its congeners by the position of the spermathecal openings in CD line and aquadrangular body at tail.